(untitled) (Journal of Advanced Veterinary and Animal Research, 2019)
Objective: Jicama (Pachyrhizus erosus) fiber has been documented to exert an immunomodulatory effect both in vitro and in vivo. However, its beneficial effect against metabolic syndrome remains unknown. This study aimed to reveal whether the jicama fiber (JF) could prevent the development of diabetes and obesity caused by a high-sugar diet (HSD). Materials and Methods: The JF was isolated from its tuberous part and subsequently used as a supplemental diet for adult male Bagg and Albino (BALB)/c mice fed with a HSD. Four different diet paradigms including normal diet, HSD (30% sucrose), and HSD in combination with 10% and 25% of JF, respectively, were deployed continuously for 8 weeks. Furthermore, the blood glucose level, glucose tolerance, body weight, food and water consumption as well as epididymal white adipose tissue (WAT) and interscapular brown adipose tissue (BAT) mass were determined. Results: Our results revealed that supplementation of 25% JF could significantly prevent the blood glucose increase, excessive body weight gain, and glucose intolerance in mice fed with HSD. Moreover, 10% and 25% JF blunted the HSD-induced WAT mass gain but failed to counteract the depletion of BAT mass. Furthermore, the fiber supplementation elicited a minimum effect on rhythm and total food and water intake. Conclusion: The JF could effectively sustain blood glucose homeostasis as well as improve body weight and WAT mass profile against the development of diabetes and obesity caused by HSD. J. Adv. Vet. Anim. Res., 6(2): 222-230, June 2019